Plants reported as toxic to ruminants in the Brazilian northeastern semiarid region - Bezerra, José Jailson Lima; Falcão-Silva, Vivyanne Santos (Revista de Ciências Agroveterinárias, 2019)
Over the years the plant poisonings have caused significant losses to ruminant producers from various Brazilian regions, affecting the livestock sector in the country. Thus, this study aims to conduct a survey with producers, veterinarians, zootechnists, agronomists and agricultural technicians about the major plants poisoning ruminants in the Curimataú Paraibano. This study was conducted in five cities in the Curimataú Ocidental Paraibano, including Barra de Santa Rosa, Cuité, Damião, Nova Floresta and Sossego. The interviews were conducted through three structured forms, containing specific questions about poisoning cases identified in the microregion cited. To carry out this survey, a total of 30 participants were interviewed (six representatives from each city) between June and October 2016. From the data obtained from the interviews, one found the main toxic plants in Curimataú Ocidental Paraibano, from the viewpoint of those interviewed, were: Anadenanthera colubrina, Mascagnia rigida, Prosopis juliflora, and Manihot glaziovii. Many interviewees demonstrate they don't know the toxic principle of other plants present in the region and cited in the literature as responsible for poisoning in ruminants, such as: Mimosa tenuiflora, Crotalaria retusa and Solanum paniculatum. The plants Physalis angulata and Ricinus communis were mentioned as toxic, but new experiments must be carried out to prove their toxicity. These results show effective prophylactic measures are necessary in rural properties, thus preventing the occurrence of outbreaks and deaths of ruminants.